Beyond methamphetamine: Documenting the implementation of the Matrix model of substance use treatment for opioid users in a South African setting. (March 2017) - Magidson, Jessica F.; Gouse, Hetta; Burnhams, Warren; Wu, Christie Y.Y.; Myers, Bronwyn; Joska, John A.; Carrico, Adam W.
Abstract: Introduction: The Matrix model of substance use treatment has been evaluated extensively in the United States as an effective treatment for methamphetamine use disorders. Since 2007, the Matrix model has been implemented in Cape Town, South Africa, where one in four treatment-seeking individuals are primarily opioid rather than stimulant users. Yet, there has been limited data on the application of the Matrix model for other types of substance use disorders in a resource-limited setting. Methods: We compared primary opioid and primary methamphetamine users seeking treatment at the first certified Matrix model substance use treatment site in Cape Town, South Africa from 2009 to 2014 ( n  = 1863) on engagement in treatment, an important early predictor of later substance use treatment outcomes, and urine-verified abstinence at treatment exit. Results: Compared to primary opioid users, primary methamphetamine users had over 50% greater odds of initiating treatment (defined as attending at least one treatment session following intake; OR = 1.55; 95%CI: 1.24–1.94), and 4.5 times greater odds of engaging in treatment (i.e., attending at least four treatment sessions; OR = 4.48; 95%CI: 2.27–8.84). There were no significant differences in rates of urine-verified abstinence at treatment exit. Conclusions: Results suggest primary opioid users may experience additional barriers to treatment initiation and engagement in the Matrix model of substance use treatment, yet those who enter treatment are equally as likely to be abstinent at treatment exit compared to primary methamphetamine users. Findings highlight the need for additional strategies to optimize treatment initiation and engagement among primary opioid users in this setting, for instance by integrating medication-assisted treatment (e.g., methadone). Highlights: Opioid use has increased in South Africa after a methamphetamine (meth) epidemic. We compared opioid and meth users' engagement in the Matrix treatment model. Meth users were 4.5 times more likely to engage in treatment vs. opioid users. Yet, no differences were found in abstinence rates by primary substance. Strategies to enhance treatment entry and engagement among opioid users are needed.